The use of combined partial nitritation and anammox process for mainstream sewage treatment - (:unkn) unknown (Water Environment Federation, 2016)
Application of Anammox process for sewage was investigated. A partial nitritation (PN) system and an Anammox (AN) system were started up using a mixed activated sludge seed from a local sewage treatment plant (STP). PN of sewage was studied under different operating conditions. Increasing free ammonia via pH adjustment in combination with limited dissolved oxygen and low sludge retention time was identified as the best operational strategy to obtain sustainable effluent from PN which is appropriate stoichiometrically for Anammox feeding. Optimized PN and enriched AN were operated in series by continuously feeding with grit chamber effluent of a local STP. The limiting step of the whole process was identified as partial nitritation. Anammox proceeded successfully. Denitrification activity simultaneously occurring with Anammox was found heavily dependent on the quality of PN effluent. PN effluent with low organic content resulted almost complete elimination of denitrification activity in AN reactor. Copyright ©2016 Water Environment Federation.
Keywords: Anammox; Mainstream; Nitritation; Partial nitrification; Sewage